PENGARUH PROFESIONALISME GURU PAK TERHADAP MINAT BELAJAR SISWA KELAS V SD SWASTA SANTA MARIA TARUTUNG T.P. 2021/2022 - Kalanius Manullang (Pusat Riset dan Inovasi Nasional, 2023)
ABSTRACT, The purpose of this study was to find out whether there was a positive and significant effect of the professionalism of PAK teachers on the learning interests of Class V students at Santa Maria Tarutung Private Elementary School T.P.2021/2022. The population in this study were all students of Class V SD Santa Maria Tarutung T.P. 2021/2022 there are 35 Protestant Christians. The entire population was used as a sample, namely 35 people. The research data was analyzed in the following steps: 1) Testing the regression which consisted of: a) Looking for the regression equation Y over X to get the regression equation 81.18 + 0.77X, b) Obtained the value of Fcount = 5.43 > Ftable(0.05 ,1.35-2=33) = 4.17 indicates that the influence of the professionalism of PAK teachers on the learning interest of Class V students of Santa Maria Tarutung Private Elementary School T.P.2021/2022 is linear, c) The large percentage of the influence of professionalism of PAK teachers on class student learning interest V Santa Maria Tarutung Private Elementary School are: (r2) x 100% = 0.1414 x 100% = 14.14%, 2) It is known that the value of tcount > ttable is 2.333 > 2.042. From the results of the significance test, it can be concluded that the research hypothesis is accepted, namely that there is a positive and significant influence between the professionalism of PAK teachers on the learning interest of Class V students at Santa Maria Tarutung Private Elementary School T.P.2021/2022.